A Diagnostic Algorithm to Guide Operative Intervention of Zone 5 Flexor Injuries. Issue 1 (February 2022) - Alluri, Ram K.; Vakhshori, Venus; Hill, Ryan; Azad, Ali; Ghiassi, Alidad; Stevanovic, Milan
Background : Given the importance of the neurovascular structures in the volar forearm, accurate diagnosis of zone 5 flexor injuries is critical. Purpose : We sought to test the hypothesis that tendinous injury would be more likely in the distal 50% of the forearm and muscle belly injury would be more likely in the proximal 50% of the forearm. Methods : From December 2015 to December 2016, we conducted a prospective clinical study of patients 18 years and older with zone 5 flexor lacerations. We excluded those with concomitant ipsilateral injuries in flexor zones 1 to 4, multiple lacerations in flexor zone 5, prior neurovascular injuries, crush injuries, patients who underwent operative exploration prior to transfer to our facility, and patients who were unable or unwilling to provide consent. Neurovascular and musculotendinous injuries on physical examination were recorded. All patients underwent operative exploration. Physical examination accuracy and the incidence of musculotendinous and neurovascular injury in the distal 50% of the forearm were compared with the proximal 50% of the forearm. Results : The distal 50% of the forearm (group 1, n = 14) had higher probability of tendon injury (64%), whereas lacerations of the proximal 50% of the forearm (group 2, n = 5) did not result in any tendinous injuries. Rather, all patients in group 2 had muscle belly injuries. There was no difference in the rate of neurovascular injury between groups. Physical examination alone was highly accurate in diagnosing nerve injuries (93%–100%) but less accurate in diagnosing arterial injuries (79%–80%) regardless of the location of injury. Conclusions : Due to the lack of tendinous injuries in proximal zone 5 lacerations, along with the accuracy of physical examination in determining the presence of neurovascular injuries, patients with lacerations in the proximal half of the forearm, without evidence of nerve or arterial injury, can likely be observed in lieu of immediate operative exploration.